Usługi jako przedmiot podatku od towarów i usług w Polsce - Miemiec, Wiesława (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
This paper attempts to investigate and present the issue of services as part of the structural element of the subject of VAT. The article consists of two parts. In the first part, which introduces the reader to the problem, the place and special features of VAT in the system of turnover taxes were explained. The full scope of VAT with a focus on the delivery of goods was also presented. In the second part of the article, the object of research is normative definition of services within the meaning of EU regulations and national law on tax on goods and services. To establish comprehensive this issue, the object of study were also activities equated with the provision of services. In conclusion the role of statistical classifications for defining the concept of services was presented and the impact of this classification on the scope of VAT after the recent amendments to the Goods and Services Tax Act.
Keywords: podatek od towarów i usług; usługi; świadczenia usług; odpłatne świadczenie usług